Serum hepcidin level with iron profile assay might replace bone marrow iron study as a diagnostic tool for evaluation of anemia in elderly without chronic renal disease - Sukdev Manna; Sankha Shubhra Chakrabarti; Rohit Singh; Indrajeet Singh Gambhir (Journal of Family Medicine and Primary Care)
Background: The bone marrow iron study is the gold standard for differentiation of the two most common causes of anemia i.e. iron deficiency anemia (IDA) and anemia of chronic disease (ACD) in the elderly. However, it is often not feasible to do bone marrow examination (BME) in every elderly anemic patient, due to its invasive nature. Hepcidin, a liver-derived peptide, has been identified as the key systemic regulator of iron homeostasis. Our study highlights the potential diagnostic role of serum hepcidin in the evaluation of anemia in elderly. Methodology: Hundred elderly patients (≥60 years of age) having iron deficiency anemia (IDA) or anemia of chronic disease/inflammation (ACD) were the study subjects with 15 age-matched healthy controls. All patients were evaluated with history, clinical examination, routine investigations (complete blood count, liver, and kidney function tests), iron profile, and serum hepcidin. The bone marrow iron study was done in every patient to categorize them as IDA and ACD. Results and Discussion: Serum iron, TIBC, MCV, ferritin, and serum transferrin saturation values were differing significantly between IDA and ACD groups. Serum hepcidin levels can be used confidently to differentiate ACD from IDA (P value <0.001). At serum concentration, 198.82 ng/mL sensitivity of hepcidin to differentiate ACD from IDA was 93.9% and specificity was 92.2%. A subset of patients is misdiagnosed when the serum hepcidin level is used as a sole marker, and this also holds true for serum ferritin. Conclusion: Though serum hepcidin level correlates well with serum iron profile and also serum hepcidin appears to be a useful marker to differentiate ACD from IDA in terms of both sensitivity and specificity, the combined assessment of serum hepcidin and iron profile appears to be a better marker than ferritin and hepcidin alone. This could replace the use of bone marrow iron staining as a diagnostic tool in anemia in elderly.